KEEFEKTIFAN MULTIMEDIA INTERAKTIF ”BAN” BERBASIS ARTICULATE STORYLINE PADA MATA PELAJARAN IPAS DI SEKOLAH DASAR - Yusi Ferawati, Eka; Rufi’i; Reza Rachmadtullah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study developed the interactive multimedia "BAN" based on Articulate Storyline for teaching Ilmu Pengetahuan alalam dan Sosial (IPAS) on the topic of natural landscapes in elementary school students, specifically grade IV. The study aimed to test the feasibility of the product considering its effectiveness, practicality and validity. The research used a development model called ADDIE (Analysis, Design, Development, Implementation, Evaluation). The subjects consisted of 25 Grade IV students from SDN Kertajaya IV/210 Surabaya. Validation results showed the material validity at 91.11% and media validity at 91.42%. Practicality was measured through teacher surveys (92%) and student surveys (93.20%). The analysis of student learning completeness obtained a percentage of 88% with a very good category. The paired t-test results obtained a Sig. value of 0.00, indicating that the Sig. (2-tailed) value of 0.00 < 0.05, which shows that the students' learning outcomes differ significantly from the pretest and posttest data. Multimedia "BAN" can attract students' attention and make them focus on the lesson. Multimedia can also enhance the quality of learning, as evidenced by the improvement in students' learning outcomes.